Reduksi Total Inventory Cost Bahan Baku Box Panel dengan Pendekatan Material Requirement Planning (MRP) - Wafiq, Rafa Auliya; R. Muhammad, Chaznin (UNISBA Press, 2023)
Abstract. PT. Bintang Cemerlang Presisindo is a company engaged in metal fabrication and manufacturing of electrical panel boxes which was founded in 2013 PT. Bintang Cemerlang Presisindo implements a Make To Order market response strategy. Currently the company is experiencing a stockpile of raw materials at the end of 2022. The cause of this stockpile is that the purchase of raw materials has not been planned properly and the quantity ordered for raw materials has not been calculated correctly so that inventory exceeds the amount needed in the production process. Raw materials that accumulate in warehouses have an impact on increasing storage costs. This of course results in an increase in total inventory costs and total production costs that must be incurred. In addition, unused raw materials will be stored in warehouses and if stored for too long can cause these raw materials to become defective and damaged. Based on this phenomenon, the formulation of the problem in this study is